Aneurysm treatment with WEB in the cumulative population of two prospective, multicenter series: 3-year follow-up. (12th June 2020) - Pierot, Laurent; Szikora, Istvan; Barreau, Xavier; Holtmannspoetter, Markus; Spelle, Laurent; Herbreteau, Denis; Fiehler, Jens; Costalat, Vincent; Klisch, Joachim; Januel, Anne-Christine; Weber, Werner; Liebig, Thomas; et al.
Abstract : Background: WEB treatment is an endovascular approach for wide-neck bifurcation aneurysms that has demonstrated high safety and good efficacy in mid-term follow-up. While evaluating safety in the long term is important to determine if delayed adverse events occur affecting late morbidity and mortality, the most important point to evaluate is the long-term stability of aneurysm occlusion. The current analysis reports the 3-year clinical and anatomical results of WEB treatment in the combined population of two European trials (WEBCAST (WEB Clinical Assessment of Intrasaccular Aneurysm Therapy) and WEBCAST-2). Methods: Aneurysm occlusion was evaluated using a 3-grade scale: complete occlusion, neck remnant, and aneurysm remnant. Results: The safety population comprised 79 patients. The efficacy population comprised 61 aneurysms. Aneurysm locations were middle cerebral artery in 32/61 aneurysms (52.5%), anterior communicating artery in 13/61 (21.3%), basilar artery in 9/61 (14.8%), and internal carotid artery terminus in 7/61 (11.5%). No adverse events related to the device or procedure occurred between 2 and 3 years. At 3 years, complete occlusion was observed in 31/61 (50.8%) aneurysms, neck remnant in 20/61 (32.8%), and aneurysm remnant in 10/61 (16.4%). Between 1 year and 3 years, aneurysm occlusion was improved or stable in 53/61 (86.9%) aneurysms and worsened in 8/61 (13.1%). Worsening was mostly from complete occlusion to neck remnant in 6/61 (9.8%) aneurysms. The retreatment rate at 3 years was 11.4%. Conclusions: This analysis confirms the high safety profile of WEB. Moreover, evidence demonstrates the great stability of aneurysm occlusion with adequate occlusion (complete occlusion or neck remnant) in 83.6% of aneurysms. Clinical trial registration: URL: http://www.clinicaltrials.gov . WEBCAST and WEBCAST-2: Unique identifier: NCT01778322 .